Pengaruh Ekstrak Ketumbar (Coriandum Sativum) terhadap Perubahan Tekanan Darah Tikus Pasca Melahirkan - Utami, Vina Nurul; Hadisaputro, Soeharyo; Rahayu, Sri (Jurusan Keperawatan FIKES UNSOED, 2016)
Hypertension is the most commont complication during pregnancy and delivery. It causes 5-10% maternal morbidity and mortality incorporate with bleeding and infection. The Maternal mortality rate caused by hypertension is about 23,95%. Coriander seeds contain flavonoid which work as antihipypertension and diuretic. This study was to examine coriander extract several dosage on decreasing systolic on post partum rats. An experimental study with randomized pre test and post test controlled group design obvserved 30 white rat Wistar Sp which divided into 5 groups randommly. Sphyngonanometer was applied to measure the blood pressure. Paired t-test, One Way ANOVA, and Repeated Measures ANOVA were administered for data analyses. Results showed that coriander extract on 10 mg/kg BB, 20 mg/kg weight and 30 mg/kgweights dosage affected to blood pressure changes on the rat (p 0.000 ), while 20 mg/kgweights and 30 mg/kgweight had no significant effects (p 0.900). It concluded that coriander estract on dosage 30 mg/kg weight and 20 mg/kg weight did not effect significantly to decreasing rat’s blood pressure. Measuring not only systole pressure was recommended for further studies.